2021
DOI: 10.1111/jch.14196
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of choroidal thickness with pulsatile hemodynamics in essential hypertensive patients

Abstract: Traditionally, the retina has been considered as the easiest accessible window to study the state of the systemic microcirculation, 1 even if the choroid is the most important vascular layer of the eye, which thinning may be due to microvascular damage, reflecting the local expression of a more generalized vascular injury. [2][3][4] Recent studies have associated changes in the thickness of the choroid with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…Similar to what happens in the kidneys, arterial stiffness might predispose choroidal circulation to increased hemodynamic pressure, with consequent local damage and reduced ChT. In line with this concept, significant inverse relationships of ChT with PWV [ 70 ] as well as with aortic PP [ 76 ] have been reported.…”
Section: Retinal and Glomerular Vasculature: Two Sides Of The Same Coinmentioning
confidence: 87%
“…Similar to what happens in the kidneys, arterial stiffness might predispose choroidal circulation to increased hemodynamic pressure, with consequent local damage and reduced ChT. In line with this concept, significant inverse relationships of ChT with PWV [ 70 ] as well as with aortic PP [ 76 ] have been reported.…”
Section: Retinal and Glomerular Vasculature: Two Sides Of The Same Coinmentioning
confidence: 87%
“…155 Over time, increased pulsatility in penetrating small blood vessels as a result of conduit artery stiffening and increased pulse pressure induces microvascular injury leading to remodelling, endothelial dysfunction, and ischaemia as discussed earlier in this paper, and rarefaction of smaller arterioles and capillaries. 156 Mulè et al studied 158 consecutive hypertensive subjects and found choroidal thinning with higher 24-hour pulse pressure that reflects arterial stiffness. 156 Thus, choroidal hyperperfusion may be followed by injury resulting from both increased flow, 155 and enhanced pulsatility contributing to further injury.…”
Section: Hypertensive Choroidopathymentioning
confidence: 99%
“…156 Mulè et al studied 158 consecutive hypertensive subjects and found choroidal thinning with higher 24-hour pulse pressure that reflects arterial stiffness. 156 Thus, choroidal hyperperfusion may be followed by injury resulting from both increased flow, 155 and enhanced pulsatility contributing to further injury. This is followed by the effect of the myogenic reflex that induces vasoconstriction and impaired perfusion and tissue exchange, with enhanced oxidative stress in the vascular wall, all leading to microvascular rarefaction, reduced flow and choroidal thinning as a later expression of chronic hypertension.…”
Section: Hypertensive Choroidopathymentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is confirmed by Mulé and coauthors in the present issue of Journal of Clinical Hypertension. 13 In this paper, Mulé explored choroidal thickness in 155 hypertensive patients undergoing a 24‐hour ambulatory blood pressure monitoring for the evaluation of central and brachial 24 hour‐pulse pressure. 14 Patients with a central pulse pressure > 35 mm Hg exhibited a thinner choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%